The Wraths of Fire : Contagion Heuristic and Intuitive Personification Processes in Early Modern Finnish-Karelian Conceptions of Illness - Kohonen, Siria (Journal for the Cognitive Science of Religion, 2022)
The way people understand and encounter illnesses include influences from human cognition as well as from their cultural surroundings. A conception of illness termed “the wraths of fire” (tulen vihat in Finnish) was a general explanation for severe skin burns in early modern Finland and Karelia, and it included ideas about personified fire and its magically contagious essence. However, the academic conversation on this notion has mostly concentrated on the socio-cultural influences behind it. In this article, I argue that the intuitive level of human cognition (e.g., Kahneman and Frederick 2005; Evans and Frankish 2009) has formed the basic guidelines for this conception of illness. The research materials consist of approximately six hundred archive units of narrated memories on healing events and healing instructions. As the materials are not based on empirical observations by the author, the article also introduces certain methodological questions important for connecting the cognitive perspective with historical materials, such as questions on the reliability of the descriptions of past events. Peer reviewed